Garden cities and the English new towns: foundations for new community planning (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2016)
The postwar new towns in England were initiated by the New Towns Act of 1946, a keystone in the reconstruction of Britain after the Second World War. Further and mostly smaller new town designations were to follow during the first half of the 1960s. It was the 1965 New Towns Act, however, which brought into existence some of the largest and most famous new towns of the postwar period. Today, over 2.6 million people live in over thirty new towns in the United Kingdom. The majority of the new towns and their citizens are in England, the most populous country in the United Kingdom.